Reporting on patients living with HIV "disengaging from care". Who is actually "lost to follow-up"?. Issue 1 (2nd January 2021) - Krentz, Hartmut B.; McPhee, Paul; Arbess, Gordon; Jackson, Linda; Stewart, Ann M.; Bois, Daniel; Rourke, Sean B.
ABSTRACT: Retention in care remains an important concern for health care providers. However, accurately identifying who is or is not retained in care can be problematic. Not all patients believed to be engaged in care are actually in care, and not all patients believed to be disengaged are truly disengaged. Identifying the status of individuals within populations is important for clinical, administrative and surveillance concerns. As part of the Linkage and Retention in Care Project at St Michael's Hospital in Toronto, Canada, we investigated the status of patients diagnosed with HIV. Detailed investigation determined who was actually Lost-to-Follow-Up (i.e., disengaged from care >12 months) and who had disengaged for known reasons. This approach determined more precisely who was currently followed in care and who was not, and to target efforts to contact and reengage patients more effectively. This study illustrates the importance of accurately monitoring populations enhancing disease management.